Progressive, Fluctuated and Regressive Resistance Training and its Impact on Lower Extremity Strength - George Abraham2; Gobind Singh3, P.S. Sankaranarayanan1 (Recent Research in Science and Technology, 2011)
The purpose of the study was to analyze the progressive, fluctuated and regressive resistance training and its impact on lower extremity strength. Eighty physically active and interested high school students (N=80) were randomly selected as subjects and their age ranged between 14 and 18 years. The selected subjects were randomly assigned into four equal groups with twenty subjects each (N=20). Group I was involved with progressive resistance training (PRG), group II was given fluctuated resistance training (FRG), group III was given regressive resistance training (RRG) and group IV acted as control (CG). The experimental groups underwent their respective experimental treatment for eight weeks 3 days per week and a session on each day. Control group was not exposed to any specific training apart from their curriculum. Leg strength was taken as variable for this investigation. The pre and post test were conducted one day before and after the experimental treatment. Analysis of covariance (ANCOVA) was used to analyze the collected data. Scheffe’s test was used as a post hoe test to determine which of the paired mean difference significantly. The results revealed that progressive and fluctuated resistance training (PRG and FRG) produced significant difference (P ≤ 0.05) on leg strength as compared to control group (CG). However regressive resistance training (RRG) produced insignificant difference (P ≥ 0.05) on leg strength as compared to control group (CG).